Social networking - Friedman, Lauri S. (Detroit : Greenhaven Press, 2011)
Describes the benefits and dangers of online social networking, its effect on young people, safety issues, cyberterrorism, and the future of online social networking
Includes bibliographical references and index
Keywords: Online social networks